Teacher Adaptation to the Merdeka Curriculum: A Case Study of Islamic Education in Primary Schools - Anie Rohaeni (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2026)
The implementation of the Merdeka Curriculum as a national education policy represents a significant phase in Indonesia’s educational reform agenda. This policy shift requires teachers to adapt not only pedagogically but also institutionally, as they function as key policy actors at the school level. This study aims to analyze how Islamic Education teachers in primary schools adapt to the transition from the 2013 Curriculum to the Merdeka Curriculum and to examine the policy implications arising from this adaptation process. Employing a qualitative approach with an education policy study design, data were collected through in-depth interviews with PAI teachers and document analysis of relevant curriculum policy texts. The data were analyzed thematically using frameworks of educational change and policy implementation. The findings indicate that while PAI teachers generally demonstrate normative acceptance of the Merdeka Curriculum’s objectives, their practical adaptation remains constrained by limited pedagogical competence in differentiated instruction, assessment literacy, and institutional support. This study concludes that the success of curriculum policy implementation depends not only on regulatory design but also on sustained systemic support that strengthens teachers’ adaptive capacity. The findings contribute to policy-oriented discussions on curriculum reform and highlight the importance of contextual professional development for teachers.